Решение уравнений. Урок 8 Уравнение (х - 1Хх – 2Xх - 3Xх – 4) +1 = 0 приведи к квадратному.
Найдите решение данного уравнения​


Решение уравнений. Урок 8 Уравнение (х - 1Хх – 2Xх - 3Xх – 4) +1 = 0 приведи к квадратному.Найдите р

protivnuy protivnuy    2   30.12.2020 10:29    0

Ответы
fedorovufa fedorovufa  29.01.2021 10:30

Объяснение:

(x-1)*(x-2)*(x-3)*(x-4)+1=0\\((x-1)*(x-4))*((x-2)*(x-3))+1=0\\(x^2-5x+4)*(x^2-5+6)+1=0.\\

Пусть х²-5x+4=t     ⇒

t*(t+2)+1=0

t²+2t+1=0

(t+1)²=0

t+1=0

t=-1     ⇒

x²-5t+4=-1

x²-5x+5=0

D=5\ \ \ \ \sqrt{D}=\sqrt{5} \\x_{1,2}=\frac{5б\sqrt{5} }{2} .

ПОКАЗАТЬ ОТВЕТЫ